Social media, socialization, and pursuing legitimation of police violence*. Issue 3 (16th August 2021) - Cheng, Tony
Abstract: Every day, police departments across America are executing stops, summonses, arrests, and increasingly, tweeting. Although scholarship has focused on how social media democratizes news production and information sharing for activist movements, it has yet to explore how police leverage these attributes to advance institutional interests. I argue that, beyond digital surveillance or community engagement, social media provides police with the technological capacity to pursue both daily socialization of online audiences to their worldview and legitimation in the aftermath of contested police violence. I provide evidence by adopting a qualitative approach to "big data" sources analyzing 1) all 3, 167 tweets posted by the New York Police Department in 2018; 2) the 778 Twitter replies to their most contested fatal shooting that year; and 3) a sample of 139 news articles covering this shooting over a year afterward. As public scrutiny toward police intensifies, social media represents an independent channel for police to publicize information unfiltered by traditional mass media. These findings have implications for police accountability and the episodes of police violence that do—and do not—elevate into national controversies.